Comparative evaluation of three fundamentally different analytical methods antioxidant activity determination with reference to bush tea (anthrixia phylicoides) - Mothapo, Mmaphefo Patricia (University of Limpopo, 2016)
In this study, antioxidant activity methodologies were evaluated in terms of analytical performances. The total antioxidant activity from Athrixia phylicoides leaves (Bush tea) determined using 2,2-diphenyl-1-picrylhydrazyl radical scavenging (DPPH•) method, cupric ion reducing power (CUPRAC) method and cyclic voltammetry (CV). Folin-Ciocalteu method was used to quantify total phenolic content (TPC) in Athrixia phylicoides leaves. The influence of chemical and physical parameters on the total phenolic content and antioxidant activity determination were investigated. Results from direct sample and crude sample were compared. Antioxidant activity and phenolic content from Athrixia phylicoides leaves were compared with those from commercialised green tea, black tea and rooibos tea using two chosen antioxidant capacity method with acceptable characteristics. Results from the evaluation of the methods demonstrated excellent recoveries (99 to 103%) consistently, good linearity within the calibration concentration range (R2 = 0.997) and repeatable low coefficient of variation < 5% were indicative of good precision except for CV method. The average total antioxidant activity of various extracts of Athrixia phylicoides leaves ranged from 0.039 to 0.122 mg/mL (EC50), 0.031 to 0.233 mg/mL (EC50) and 339 to 429 mV (anodic potential) for DPPH method, CUPRAC method and CV method, respectively. The total antioxidant activity values for each Athrixia phylicoides samples determined by CUPRAC method were higher than the values produced by DPPH and CV methods. The highest antioxidant activities in the DPPH and CUPRAC methods were found in water extracts (direct sample). However, concentrated samples for DPPH method and CV gave a different trend with the methanol extract (crude sample) displaying the highest antioxidant capacity. Increasing the infusion time only increased total antioxidant activity determined by CUPRAC method, whilst DPPH and CV methods had the highest antioxidant activity in the lowest infusion time (3 min). Even though the results are inconclusive with regard to the effect of solid to solvent ratio effect on the total antioxidant activity, 1:150 ratio and 1:100 ratio extracts for both CUPRAC and DPPH methods and for CV gave the highest antioxidant capacities, respectively. The total antioxidant activities in pure antioxidant standards and in the teas were ranked in the following order by both CUPRAC and DPPH methods: Quercetin > catechin > Trolox and Chinese green tea > Joko black tea > Athrixia phylicoides leaves > Laager rooibos tea, respectively. Comparative study showed the necessity of employing more than one method, as each method for the same sample yielded different results. CUPRAC and DPPH methods displayed higher sensitivity and repeatability as compared to the CV method with poor precision.
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2016
Keywords: Bush tea; antioxidant; Antioxidant; Phenolic acids